Blood flow-restricted exercise in space - Hackney, Kyle J (BioMed Central, 2012)
Prolonged exposure to microgravity results in chronic physiological adaptations including skeletal muscle atrophy, cardiovascular deconditioning, and bone demineralization. To attenuate the negative consequences of weightlessness during spaceflight missions, crewmembers perform moderate- to high-load resistance exercise in conjunction with aerobic (cycle and treadmill) exercise. Recent evidence from ground-based studies suggests that low-load blood flow-restricted (BFR) resistance exercise training can increase skeletal muscle size, strength, and endurance when performed in a variety of ambulatory populations. This training methodology couples a remarkably low exercise training load (approximately 20%–50% one repetition maximum (1RM)) with an inflated external cuff (width, ranging between approximately 30–90 mm; pressure, ranging between approximately 100–250 mmHg) that is placed around the exercising limb. BFR aerobic (walking and cycling) exercise training methods have also recently emerged in an attempt to enhance cardiovascular endurance and functional task performance while incorporating minimal exercise intensity. Although both forms of BFR exercise training have direct implications for individuals with sarcopenia and dynapenia, the application of BFR exercise training during exposure to microgravity to prevent deconditioning remains controversial. The aim of this review is to present an overview of BFR exercise training and discuss the potential usefulness of this method as an adjunct exercise countermeasure during prolonged spaceflight. The work will specifically emphasize ambulatory BFR exercise training adaptations, mechanisms, and safety and will provide directions for future research.